Hotel restaurant food delivery app: customer intention / Rashid Salleh ... [et al.] - Salleh, Rashid; Hamir, Norhamizan; Azmi, Nur Ain Nabila; Abdul Rahim Siddiqe, Ashraf Siddik Khan (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
The industry revolution has revolved the food delivery system which from restaurant-customer to customer-apps-restaurant. The fourth industrial revolution also offering opportunities for business to create a novel service offering. A company such as Food Panda, Deliver Eat, Grab Food and others has make millions of ringgit per years by providing a food delivery service (Rosli, 2018). She also added that this new business model has shown service technology will become one of important business for future market demand. Unfortunately, this profitable business model did not fascinate hotel restaurant. None of the above apps provided a food delivery from hotel restaurant in Penang. Furthermore, the hotel itself did not have any created and offer online food delivery for their hotel restaurant. Exploring this unusual phenomena, the study will investigate either there is any demand for hotel restaurant food delivery or not. In order to conduct the study, theory of acceptance model (TAM) will be use as a foundation of this search. The study objective has revealed that all restaurant customers in Malaysia will be the sample in this study. To decode the data collected, Statistical Package for the Social Sciences (SPSS) software will be use. The result of the study may provide a little help for the industry and added a significance data, which can be utilize by other researchers. Besides that, this study may add a new body of knowledge where there is still no study specifically focus on hotel restaurant segment.